In vitro antibacterial activity of antiretroviral drugs on key commensal bacteria from the human microbiota - Rubio-Garcia, Elisa; Ferrando, Núria; Martin, Núria; Ballesté-Delpierre, Clara; Miró, Jose M.; Paredes, Roger; Casals-Pascual, Climent; Vila, Jordi (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Antiretroviral therapy has improved life expectancy in HIV-infected patients. However, people living with HIV under antiretroviral therapy are at higher risks of developing chronic complications and acquiring multidrug resistant bacteria than healthy population. These factors have been associated with shifts in gut microbiome composition and immune activation. It is unclear how antiretroviral drugs affect gut microbiota composition, but it has been observed that antiretroviral treatment is not able to fully restore gut health after HIV infection. Additionally, some antiretroviral drugs have shown antibacterial activity suggesting that these drugs could have a direct impact on the human microbiome composition. Methods We determined the in vitro antibacterial activity of 16 antiretroviral drugs against a set of key clinically relevant and human commensal bacterial strains. Results Our results demonstrate that 5 antiretroviral drugs have in vitro antibacterial activity against gut and vaginal human commensal bacteria. Zidovudine has antibacterial activity against Escherichia coli, Klebsiella pneumoniae and Prevotella bivia, abacavir against Gardnerella vaginalis, efavirenz against G. vaginalis and P. bivia and bictegravir against Enterococcus spp. and G. vaginalis. Moreover, we describe for the first time that elvitegravir has antibacterial activity against G. vaginalis and P. bivia and, most importantly, against vancomycin-resistant Enterococcus spp. and methicillin-resistant Staphylococcus aureus strains with MIC values of 4-16 and 4 µg/mL, respectively showing high level of effectiveness against the tested multidrug-resistant bacteria. Discussion Our results underscore that some antiretroviral drugs may influence the human microbiota composition. In addition, we report the potential use of elvitegravir to treat multidrug-resistant Gram-positive bacteria warranting the need of clinical studies to repurpose this antiretroviral drug.